Determinan Kejadian Stunting pada Anak Balita di Wilayah Kerja Puskesmas Soromandi Kabupaten Bima Nusa Tenggara Barat (Determinan Incidence of Stunting in Children Under Five Year at Puskesmas Soromandi Bima district of West Nusa Tenggara) - Mirham Nurul Hairunis; Ninna Rohmawati; Leersia Yusi Ratnawati (Pustaka Kesehatan, 2016)
Stunting is linear growth disturbance caused by the nutrient intake of chronic malnutritionand chronic or recurrent infections showed with height z-score for age (H / A) <-2 SDbased on the standard WHO. Based on the results of Nutritional Status Monitoring inBima, the prevalence of stunting for each year has increased. The prevalence of stuntingin 2011 amounted to 23.61%, in 2012 amounted to 30.3%, and in 2013 amounted to53.2%. Soromandi district is one of the districts with the highest prevalence of stunting inBima. This study aimed to analyze the determinants of the incidence of stunting inchildren under five year in Puskesmas Soromandi Bima district of West Nusa Tenggara.This research is an observational analytic study with cross sectional approach. This studyshows that there was no significant relationship between food intake, genetic factors,status BBLR with the incidence of stunting and no significant correlation between geneticfactors with the incidence of stunting. The factors that most influence the incidence ofstunting was exclusive breastfeeding.Keywords: Stunting, Children Under Five Year, Determinan